Higher climate warming sensitivity of Siberian larch in small than large forest islands in the fragmented Mongolian forest steppe. (28th June 2017) - Khansaritoreh, Elmira; Dulamsuren, Choimaa; Klinge, Michael; Ariunbaatar, Tumurbaatar; Bat‐Enerel, Banzragch; Batsaikhan, Ganbaatar; Ganbaatar, Kherlenchimeg; Saindovdon, Davaadorj; Yeruult, Yolk; Tsogtbaatar, Jamsran; Tuya, Daramragchaa; Leuschner, Christoph; et al.
Abstract: Forest fragmentation has been found to affect biodiversity and ecosystem functioning in multiple ways. We asked whether forest size and isolation in fragmented woodlands influences the climate warming sensitivity of tree growth in the southern boreal forest of the Mongolian Larix sibirica forest steppe, a naturally fragmented woodland embedded in grassland, which is highly affected by warming, drought, and increasing anthropogenic forest destruction in recent time. We examined the influence of stand size and stand isolation on the growth performance of larch in forests of four different size classes located in a woodland‐dominated forest‐steppe area and small forest patches in a grassland‐dominated area. We found increasing climate sensitivity and decreasing first‐order autocorrelation of annual stemwood increment with decreasing stand size. Stemwood increment increased with previous year's June and August precipitation in the three smallest forest size classes, but not in the largest forests. In the grassland‐dominated area, the tree growth dependence on summer rainfall was highest. Missing ring frequency has strongly increased since the 1970s in small, but not in large forests. In the grassland‐dominated area, the increase was much greater than in the forest‐dominated landscape. Forest regeneration decreased with decreasing stand size and was scarce or absent in the smallest forests. Our results suggest that the larch trees in small and isolated forest patches are far more susceptible to climate warming than in large continuous forests pointing to a grim future for the forests in this strongly warming region of the boreal forest that is also under high land use pressure. Abstract : We examined the influence of stand size and stand isolation on the growth performance of larch in forests of four different size classes located in a woodland‐dominated forest‐steppe area and small forest patches in a grassland‐dominated area. We found increasing climate sensitivity and decreasing first‐order autocorrelation of annual stemwood increment with decreasing stand size. Stemwood increment increased with previous year's June and August precipitation in the three smallest forest size classes, but not in the largest forests.